2019
DOI: 10.2139/ssrn.3438365
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Topographic Maps in Human Association Cortex Hierarchically Transforms Visual Timing-Selective Responses

Abstract: Highlights d Many brain areas show neural responses to specific ranges of visual event timing d Timing preferences change gradually in these areas, forming topographic timing maps d Neural response properties hierarchically transform from visual to premotor areas d Timing, numerosity, and visual field map networks are distinct but largely overlap

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous studies have pointed to a broad network of neural regions engaged in temporal processing, including the supplementary motor area (SMA), inferior frontal gyrus (IFG), cerebellum and basal ganglia (Wiener et al, 2010b;Hayashi et al, 2014Hayashi et al, , 2018Protopapa et al, 2019;Harvey et al, 2020). Although the ROI approach utilized here was designed to focus on right SMG, it is noteworthy that none of these cortical or subcortical areas showed duration-selective attenuation of the BOLD response in the exploratory, whole brain analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed to a broad network of neural regions engaged in temporal processing, including the supplementary motor area (SMA), inferior frontal gyrus (IFG), cerebellum and basal ganglia (Wiener et al, 2010b;Hayashi et al, 2014Hayashi et al, , 2018Protopapa et al, 2019;Harvey et al, 2020). Although the ROI approach utilized here was designed to focus on right SMG, it is noteworthy that none of these cortical or subcortical areas showed duration-selective attenuation of the BOLD response in the exploratory, whole brain analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the processes underlying subjective time have their neural substrates in perceptual and memory systems, not systems specialized for time itself. Other recent studies of time perception (21,23,41,42) have attempted to correlate maps of neural activity with a specific timing-related behavior, responses, or physical elapsed durations. In contrast, we have taken a model-based approach to describe how sensory information arriving in primary sensory areas is transformed into subjective time.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent evidence revealed a clear gradient organization along the anterior-posterior axis of SMA, with anterior and posterior SMA sub-regions showing preferential activations for short and long durations, respectively (Protopapa et al, 2019; see also Harvey et al, 2019). This durationsensitive tuning organized in a gradient might be a good candidate to sequentially integrate temporal pulses into a representation of durations.…”
Section: Common Neural Network For Space and Timementioning
confidence: 93%
“…For example, a study showed that, similar to visual cortex, human fronto-parietal cortices contain topographic representations of eccentricity and polar angle, which are organized into clusters so that to represent all the gradients of polar angle of the contralateral visual field (Mackey, Winawer, & Curtis, 2017). Likewise, very recent evidence identified topographic timing maps or chronotopic maps in several brain regions, including not only sensory cortices but also frontal, parietal areas and SMA (Harvey, Damoulin, Fracasso, & Paul, 2019;Protopapa et al, 2019).…”
Section: 'Gradiatom': Functional Gradients Underlying Space and Timementioning
confidence: 99%